ANALYSIS CALCULATION OF DEPRECIATION FIXED ASSETS ACCORDING TO FINANCIAL ACCOUNTING STANDARDS AND TAX LAWS AS WELL AS IMPACT ON TAXABLE INCOME IN PT. MASSINDO SINAR PRATAMA MANADO - Goni, Yuvita M. F; Budiarso, Novi Swandari (Universitas Sam Ratulangi, 2018)
Calculation of depreciation fixed assets according to financial accounting standards using five methods: the straight-line method, declining balance method, sum of the years digit method, service hours method, and the unit of productions method. While according to taxation rules just only use two method: the straight-line method and the declining balance method. The differences in the use of depreciation methods according to financial accounting standards and tax rules will result in fiscal correction. According to the depreciation expense is deductible expense for purpose of calculating income tax. The purpose of this study was determine the application of methods of depreciation fixed assets according to financial accounting standards and tax laws as well as impact on taxable income PT. Massindo Sinar Pratama Manado. The analytical method used is descriptive qualitative analysis method. The results showed the application of the method of calculation of depreciation PT. Massindo Sinar Pratama Manado in accordance with the provisions of the tax, but an error in the calculation of depreciation that increase the value of the company taxable income. PT. Massindo Sinar Pratama Manado should be more careful and referring to the tax rules in calculating the value of depreciation due to give effect to net profit before tax (taxable income) of the company, so that it will also to give effect to income tax to be paid by the company. Keywords : depreciation, fixed assets, financial accounting standards, tax rules, taxable income